Diseño de un cuento interactivo para apoyar la enseñanza de la lectura en niños sordos (2018)
The development of skills and abilities such as reading in children plays an important role in society, because in these stages is where a solid base is formed to face the challenges of everyday life, this is why it must take into account the population range of deaf children, since new challenges arise to achieve these skills. The proposal of this research work is oriented to the creation of an interactive story that supports the teaching of reading for deaf children, performing the analysis of the profile of the deaf infant in the educational environment and selecting necessary aspects to analyze, such as creation of the story, learning style, advantages that the use of the story brings, elements of story creation, the use of ICT in pedagogical methodologies, among others. The creation of an interactive story will serve as support material for the teaching of reading and writing skills for deaf children. The participants will be deaf children at the Club de Leones de Cali San Fernando ITES, where different analyzes of this population range and the development with motivating methodologies that involve the use of ICT are obtained.